Peran Pendamping Proses Produk Halal dalam Memberdayakan Ekonomi Usaha Mikro dan Kecil: - Fitriyani; Sabiruddin, Sabiruddin (Islamic Management and Empowerment Journal, 2026)
Halal Product Process Assistance (PPH) is someone who is trained to provide assistance to business actors to obtain halal certificates. This study aims to first, explain the role of the Halal Product Process Assistance (P3H) as an economic empowerment for Micro and Small Enterprises (MSEs). Second, the extent to which halal certification can empower the economy of MSE actors. This research uses qualitative research methods with library data collection techniques, namely research activities carried out by collecting information and data with the help of various kinds of materials in online and offline libraries such as reference books, previous research results, articles, notes, and various journals. The results of this study are first, the activities of the Halal Product Assistance (PPH) are an effort to empower the economy, this is in accordance with the theory of empowerment by Zubaedi regarding the role of assistants in economic empowerment, namely as Motivators, Communicators and Facilitators. Second, halal certification can empower the economy can be seen from 3 implications of halal certification, namely increasing consumer confidence, increasing market share, and increasing business competitiveness.